Recycling Networks. Grassroots Resilience Tackling Climate, Environmental and Poverty Challenges - Oloko, Michael (JOOUST, 2021)
The project brings together monetary and grassroots innovation studies in interdisciplinary research, contributing to the development and diffusion of financial and monetary infrastructures for urban informal settlements, and indicating a novel route for social enterprise and development aid.